La autogestión del Trabajo Social y la perspectiva del investigador - Barbero, J. Manuel (Cuadernos de Trabajo Social, 2006)
The intents to delimit what is research in Social Work are always approximate. To establish the investigations that are more useful for Social Work can be convenient to recall the conditions that offer disciplinary character to their practices: elements that would endow of scientific orientation to the Social Work exercise. The author carries out a brief one travel through those elements that make operational the presence of the scientific method (the procedure structure, the sources of scientific information, the presence of the planning paradigm, the theorisation into the intervention projects).